Kerugian ekonomi dari sisa makanan konsumen di rumah makan dan potensi upaya pengurangan sampah makanan - Amelia Hasanah; Eka Intan Kumala Putri; M Ekayani (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Restaurant’s consumers become one of the biggest food waste producers. With the increasing number of population and restaurants in Dramaga District, Bogor Regency, it is very possible that the amount of food waste generated also increases. The driving factors for consumers to waste their food could be the bad eating habits, poor restaurant management and the lack of knowledge about its negative effects towards environment, social and economic. This study aimed to evaluate the amount of plate-waste, to estimate the economic losses of plate-waste and to determine the best effort in reducing consumer’s food waste. This research was conducted in Dramaga District, Bogor Regency. The methods use in this research were Measurement and Calculation by SNI 19-3964-1994, conversion factor and Weighted Sum Model (WSM). The result shows that the total of food waste generated from consumers were 75,825,96 kg/year. The economic losses based on the raw price of food ingredients were IDR 1,011,743,415 per year, based on the selling price of food were IDR 5,138,912,541 per year and based on production cost were IDR 4,111,130,033 per year. The priority strategi to be applied in reducing consumer food waste was by prevention.